Peran Pimpinan Pusat Pelatihan Quail Farm Dalam Pemberdayaan Ekonomi Masyarakat - Puspa Tresna Winanti; Agus Ahmad Safei; Luk Luk Atin Marfuah (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2022)
Poverty of the farming community due to minimum salaries and lack of use of technology. then the lack of resources for young farmers who are involved in the agricultural sector. therefore the leadership opened a training center to facilitate the community to be free from the problem of poverty as well as create new farmers. The aim of the research is to find out how the effort, supervision and results of the role of the leadership of the quail farm training center are in empowering the community's economy. The method used is descriptive method with a qualitative approach. The results of the study explained that the efforts made by the leadership of the training center were to open an agricultural training center with training/apprenticeship programs and quail entrepreneurship, working with various related agencies and business actors, conducting egg lab tests and promotions, and becoming consultants. management supervision with two accesses, namely in farm and out farm. the result of the leadership role is to produce new breeders, the people who have done the training have their own income and the surrounding community also has permanent jobs.